Microstructure Study of the Stainless Steel Layer on AlSi Cast Alloy Prepared by Laser Deposition - Michna, Stefan; Hren, Iryna; Michnova, Lenka; Lattner, Michal (Manufacturing Technology Journal, 2019)
The main aim of this study is structural changes on the layer of Al-Si cast alloy by laser austenitic stainless steel 17 246 deposition. In order to remelt the Al-Si alloy surface the laser of 1, 9 kW has been used for facing area, and 1.6 kW for the edge. The linear laser scan rate of the beam was set 450 mm.min-1 for facing area, and for the edge 550 mm.min-1. We observed that the thin surface made of austenitic stainless steel had a lot of splits. The purpose of this study is also to enhance inherent properties of the surface materials to create new product or improve on existing one.
Keywords: laser stainless steel deposition; austenitic stainless steel 17 246; Al-Si cast alloy; microstructure of layer; fusion; splits